Law Enforcement By The Satpol PP Against Violations Of Regional Regulation Number 10 Of 2021 Concerning The Control, Supervision And Restrictions Of The Distribution Of Alcoholic Beverages Without A Permit In Karawang Regency - Ramadani, Trisna; Guntara, Deny; Abas, Muhamad (Journal of Law, Politic and Humanities, 2025)
The distribution of alcoholic beverages without a permit in Karawang Regency has become a serious issue affecting public order and community health. To address this matter, the local government enacted Regional Regulation Number 10 of 2021 concerning the Control, Supervision, and Restriction of Unlicensed Alcoholic Beverages. This study aims to examine the regulation on the control, supervision, and restriction of unlicensed alcoholic beverages in Karawang Regency, as well as the law enforcement efforts by Civil Service Investigators (PPNS) of the Karawang Public Order Agency (Satpol PP), and the obstacles faced in implementing the regulation. This research uses a qualitative method with a descriptive approach. Data collection techniques include interviews and observations. The results of the study indicate that The regulation on the control, supervision, and restriction of unlicensed alcoholic beverages in Karawang Regency is governed by Regional Regulation Number 10 of 2021, which classifies alcoholic beverages into Group A, Group B, and Group C. It also stipulates administrative sanctions in Article 16, including written warnings, temporary business closures, business license revocations, and business closures. Criminal sanctions are regulated in Article 18, which states that violators may be fined up to IDR 50,000,000 (fifty million rupiahs) or face imprisonment for up to 3 (three) months. Law enforcement efforts by the Karawang Satpol PP against violations of Regional Regulation Number 10 of 2021 are carried out through field operations, confiscation of evidence, and the imposition of sanctions. In addition, PPNS officers prepare investigation reports and coordinate with the public prosecutor’s office for further legal proceedings. The challenges faced include the lack of authority to detain suspects by PPNS officers, lengthy investigation processes due to the need for coordination with the prosecutor’s office, and changes in administrative systems such as the implementation of the e-Berpadu application, which requires official letters for searches and seizures.